Fluid-structure simulation of a left ventricle with dilated cardiomyopathy / Chan Bee Ting - Chan, Bee Ting (2013)
Dilated cardiomyopathy (DCM) is the most common myocardial disease which not only leads to systolic dysfunction but also diastolic deficiency. In the present work, the effect of DCM on the intraventricular fluid dynamics and myocardial wall mechanics were investigated. In addition, the individual effect of parameters related to DCM on several important fluid dynamics and myocardial wall mechanics variables during ventricular filling were also studied. Intraventricular fluid dynamics and myocardial wall deformation are significantly impaired under DCM conditions, which were demonstrated by low vortex intensity, flow propagation velocity (Vp), intraventricular pressure difference (IVPD), and strain rates, but high end diastolic pressure (EDP) and wall stress. The sensitivity analysis results showed that Vp substantially decreases with an increase in wall stiffness, and is relatively independent of preload at low peak E-wave velocity. Early IVPD is mainly affected by the rate of change of the early filling velocity and end systolic volume (ESV) which changes the ventriculo:annular proportion. Regional strain rate, on the other hand, is significantly correlated with regional stiffness, and therefore forms a useful indicator for myocardial regional ischemia. This study enhanced understanding of the mechanisms leading to clinically observable changes in patients with DCM.